2019
DOI: 10.21292/2075-1230-2019-97-2-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Respiratory Muscle Strength in Those With Asthma, Chronic Obstructive Pulmonary Disease and Combination of These Two Conditions

Abstract: ФГАОУ ВО «Дальневосточный федеральный университет» Минобрнауки России, г. Владивосток, РФ 2 ФГБОУ ВО «Владивостокский государственный университет экономики и сервиса» Минобрнауки России, Институт информационных технологий, г. Владивосток, РФ Цель исследования: сравнительная оценка силы дыхательных мышц (ДМ) у больных бронхиальной астмой (БА), хронической обструктивной болезнью легких (ХОБЛ) и с их сочетанием, определение информативности ее индикаторов для верификации этих состояний. Материалы и методы. В стаци… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Correlation analysis showed that respiratory muscle strength depends on the severity of bronchial obstruction, lung hyperinflation, skeletal muscle mass, body mass index, respiratory discomfort and functional status of patients. The comparative analysis of several regression models showed that the MEP/MIP ratio proves the feasibility of its use as an additional tool for verifying various clinical variants of bronchial obstruction [33][34][35].…”
Section: Telemedicine Diagnosismentioning
confidence: 99%
“…Correlation analysis showed that respiratory muscle strength depends on the severity of bronchial obstruction, lung hyperinflation, skeletal muscle mass, body mass index, respiratory discomfort and functional status of patients. The comparative analysis of several regression models showed that the MEP/MIP ratio proves the feasibility of its use as an additional tool for verifying various clinical variants of bronchial obstruction [33][34][35].…”
Section: Telemedicine Diagnosismentioning
confidence: 99%